Presidential diplomacy: an analysis of the Indo-African relationship and of Africa as a priority in Indian foreign policy - Godoy, Jhonathan; Silva Lage, Maria Clara (Fronteira: revista de iniciação científica em Relações Internacionais, 2022)
Presidential diplomacy is usually a measure of the degree of a country’s diplomatic activity, indicating which actors are preferred by it in the international arena. However, quantitative studies on presidential diplomacy from countries in the Global South are still scarce. The purpose of this article is to look at Indian presidential diplomacy, focusing on its relationship with the African continent compared to other continents. For the development of the study, the RPDN - Rising Powers Diplomatic Network dataset was used and, through its use, we observed the degree of presidential diplomacy performed by India and how Africa fits into this panorama in the period 1995 - 2019. Results indicate that although Africa is an extremely relevant actor for India, other continents received a higher numerical value of Indian visits, demonstrating a greater degree of interest within the scope of India's foreign policy.